Outcomes and Differences by Occluded Vessel after Endovascular Thrombectomy for Isolated Medium Vessel Occlusions - Matsukawa, Hidetoshi (2024)
Background: The outcomes of endovascular thrombectomy (EVT) for medium vessel occlusions (MeVOs) of specific vascular territories remain unknown. We aimed to investigate EVT outcomes by MeVO locations using the data from an ongoing international multicenter registry. Methods: Patients with isolated MeVO who underwent EVT between January 2013 and December 2022 were retrospectively analyzed. Isolated MeVO was defined as an occlusion of the A2 or A3 (A2/A3), M2 or M3, and P2 or P3 (P2/P3). Outcomes included a 90-day modified Rankin score (mRS) of 0-2, successful recanalization (modified Thrombolysis in Cerebral Infarction score ≥ 2b), early neurological deterioration (END) or improvement (ENI), and 90-day mortality. END was defined as a worsening of ≥4 points from the baseline National Institutes of Health Stroke Scale (NIHSS) score within 24 h of EVT, while ENI was defined as an improvement of ≥4 points from the baseline NIHSS score within 24 h of EVT. Results: 1744 MeVOs included. Compared to M2 occlusions (n = 1542, 88.4%), A2/A3 (n = 36, 2.1%) occlusions had lower odds of 90-day mRS 0-2 (adjusted odds ratio [aOR] 0.30, 95% confidence interval [CI] 0.11-0.80), and P2/P3 occlusions (n = 49, 2.8%) had lower odds of successful recanalization (aOR 0.19, 95% CI 0.07-0.50), and higher odds of END (aOR 3.53, 95% CI 1.35-9.25). Other outcomes showed no significant differences. Conclusions: A2/A3 occlusions were more likely to have worse outcomes compared to M2 occlusions after EVT for patients with isolated MeVOs.